Respond to this Question
Similar Questions

Trig
Verify the identity: tanx(cos2x) = sin2x  tanx Left Side = (sinx/cosx)(2cos^2 x 1) =sinx(2cos^2 x  1)/cosx Right Side = 2sinx cosx  sinx/cosx =(2sinxcos^2 x  sinx)/cosx =sinx(2cos^2 x 1)/cosx = L.S. Q.E.D.
asked by Ashley on April 14, 2007 
Math (trigonometry)
Trigonometry identities are so hard... I need some help proving these identities: *Oh, and I'm only in grade 11, so the identities we use are quotient identity and Pythagorean identity. sinx/(sinx + cosx) = tanx/(1 + tanx) cos^2x
asked by Lucy on April 13, 2008 
math
solve each equation for 0=/
asked by sh on February 15, 2009 
PreCalculus
How can this identity be proved/verified? cscxsinx=1/(secxtanx) I have tried starting on both sides of the equation to get to the other. By starting on one side of the equation and manipulating it to make it look like the other
asked by Corin on May 3, 2007 
trigonometry
can i use factoring to simplify this trig identity? the problem is sinx + cotx * cosx i know the answer is cscx and i know how to get it but i want to know if i can do factoring to get it bc i tried to but it wont give me the
asked by v on December 3, 2012 
trig
find the exact solutions 2cos^2x+3sinx=0 the way it stands, that is a "nasty" question. Are you sure the second term isn't 2sin(2x) ? no, its as i wrote it. then it's got me stymied, I must be missing something rather obvious,
asked by Devon on April 16, 2007 
Trig
prove the identity (sinX)^6 +(cosX)^6= 1  3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1cosX^2)^3 = (12CosX^2 + cos^4) (1cosX^2) then multiply that out 12CosX^2 + cos^4  cosX^2 + 2cos^4 cos^6 add that on the left to the cos^6,
asked by JungJung on December 8, 2006 
Trigonometric
sin3x=(sinx)(3asin^2x) Wow! is that arcsin^2(x) ??? are we solving for x? or is it proving the identity? proving the identity sin3x=(sinx)(3sin^2x) Your identity is wrong, it should say: sin3x=(sinx)(34sin^2x) try this: sin(3x)
asked by abdo on May 3, 2007 
Trig Help
Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)] =[sinx+sin^2x]/[sinx+1] =[sinx+(1cos^2x)]/[sinx+1] =??? This is where I'm stuck. Can someone help me.
asked by Anonymous on March 11, 2012 
Math
Radical ((1sinx)/(1+sinx))= (1sinx)/cosx (absolute) Identity identity
asked by Anonymous on December 11, 2014